The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1089/zeb.2014.1021
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Efficacy of Emamectin Benzoate and Ivermectin for the Treatment of Pseudocapillaria tomentosa in Laboratory Zebrafish (Danio rerio)

Abstract: Tolerance of adult zebrafish and efficacy of emamectin benzoate and ivermectin in eliminating Pseudocapillaria tomentosa infection were evaluated. In the tolerance study, behavioral changes, fecundity, histopathology, and mortality were evaluated for in-feed administration of emamectin (0.05, 0.10, and 0.25 mg/kg) and ivermectin (0.05 and 0.10 mg/kg). All doses of emamectin were well tolerated. Ivermectin 0.05 mg/kg administration resulted in mild behavioral changes and a transient decrease in fecundity. Iverm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 18 publications
3
40
1
Order By: Relevance
“…In a study where single-housed fish kept in a barren environment were compared with those in an enriched (i.e. greenery added) environment, there was no difference observed in the novel tank diving or light-dark preference tests [7]. Given our experimental design we cannot completely rule out the contribution of the greenery, but in light of the existing data in the literature, we think that fish density plays the primary role in determining the difference in anxiety phenotype.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a study where single-housed fish kept in a barren environment were compared with those in an enriched (i.e. greenery added) environment, there was no difference observed in the novel tank diving or light-dark preference tests [7]. Given our experimental design we cannot completely rule out the contribution of the greenery, but in light of the existing data in the literature, we think that fish density plays the primary role in determining the difference in anxiety phenotype.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the lack of differences in bottom-dwelling among the four housing conditions, Collymore and colleagues [7], nevertheless, concluded that housing fish individually in a barren environment enhances anxiety and that enrichment It would appear that previously under-valued aspects of experimental design may influence, in subtle ways, the data obtained, particularly when behavioral parameters are being measured. While testing conditions often receive the highest attention, methods used for housing and handling may be currently insufficiently emphasized or inadequately reported.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Transmission can occur in as little as 1 month. 44 P. tomentosa has also been associated with an increased incidence of tumor formation in zebrafish exposed to carcinogens. 2 As more zebrafish are being used for cancer research, this is another possible confounding agent.…”
Section: Choice Of Agentsmentioning
confidence: 99%
“…Three recent publications described effective treatments for zebrafish infected with this parasite. [44][45][46][47] These include use of fenbendazole, ivermectin, emamectin benzoate, mebendazole and praziquantel.…”
Section: Choice Of Agentsmentioning
confidence: 99%